Eat right your guide to maintaining a healthy diet - Schrier, Allyson Valentine (Mankato, Minn Capstone Press, 2012)
"An introduction to healthy eating habits, including the food pyramid, basic nutrition, and tips on making healthy choices"--
The world around us (human body)
Includes bibliographical references (p. 31) and index
"RL: 3-4; IL: 3-9"--P. [4] of cover
1 2 13
NEW_ZTN_GN
Keywords: Food -- Juvenile literature; Nutrition -- Juvenile literature